Low-voltage-driven organic phototransistors based on a solution-processed organic semiconductor channel and high k hybrid gate dielectric. Issue 38 (21st September 2017) - Jiang, Bo-Yi; Vegiraju, Sureshraju; Chiang, Anthony Shiaw-Tseh; Chen, Ming-Chou; Liu, Cheng-Liang
Abstract : Low-voltage-driven organic phototransistors integrate the photodetector and photomemory functions within one single device to precisely sense the brightness and carry out multilevel memory operations. Abstract : Solution-processed micro-ribbon shaped organic semiconductors and high k hybrid gate dielectric were fabricated for low-voltage-driven organic phototransistors, which integrate the photodetection and memory properties within one single device.